Organizational culture and employee performance: moderation effect of transformational leadership style / Solomon Ozemoyah Ugheoke - Ugheoke, Solomon Ozemoyah (Universiti Teknologi MARA, Cawangan Melaka, 2019)
The study examined the relationship between organizational culture and employee performance: moderation effect of transformational leadership style. The present study was designed to use a survey research method in studying organizational culture and employee performance: moderation effect of transformational leadership style. The units of analysis were the selected employees of ministry of higher education in Oman. Random sampling procedures was used which consisted of 250 employees drawn from employee identification numbers in the data base of the ministry of education in Oman. Multiple and Hierarchical regression analysis was employed to test the hypotheses. Result showed that supportive and bureaucratic culture has significant positive influence on employee performance. The findings also revealed that innovative culture does not influence employee’s performance in the context of public sector. Additionally, moderating effect of transformational leadership style was found. The study significantly contributes to culture literature by the inclusion of transformational leadership style as a moderator. Another contribution is the relative paucity of research regarding organizational culture and employee performance in the public sector. Hence, enhancing employee’s performance require managers to improve the culture of their organization to match organizations dynamic environment, understanding that certain types of culture and the type of leadership style employed by managers will help to enhance the cohesiveness of members and subsequently their performance. Thus, organizational culture should play a prominent role before employee’s recruitment. Managers should also be concerned with designing meaningful tasks and drawing up plans to promote culture.